Advancing Stock Market Predictions with Time Series Analysis including LSTM and ARIMA - Ahammad, Ishtiaq; Ankan Sarkar, William; Akter Meem, Famme; Ferdus, Jannatul; Ahmed, Md. Kawsar; Rahman, Md. R.; Sultana, Rabeya; Islam, Md. Shihabul (Cloud Computing and Data Science, 2024)
Predicting stock market prices accurately is a major task for investors and traders seeking to optimize their decision-making processes. This research focuses on the comparative analysis of advanced machine learning (ML) techniques, particularly the Long Short-Term Memory (LSTM) model and Autoregressive Integrated Moving Average (ARIMA) model, for predicting stock market prices. The study involves thorough data collection and preprocessing to ensure the quality and reliability of the historical stock price data, forming a robust foundation for the predictive models. The core contribution of this paper lies in its systematic and comparative analysis of these two models. A range of performance metrics, including Mean Absolute Error (MAE) and Root Mean Square Error (RMSE), is employed to assess and contrast the predictive accuracy and efficiency of the LSTM and ARIMA models. The research findings indicate that the ARIMA model, contrary to expectations, outperforms the LSTM model in this study, achieving lower RMSE and MAE values. Specifically, the ARIMA model demonstrates a Test RMSE of 4.336 and a Test MAE of 3.45926, indicating its superior predictive accuracy compared to the LSTM model. Furthermore, the study sets its findings against the backdrop of existing literature by comparing the performance of its models with those reported in previous research. This comparison shows better results achieved by our stock market prediction models. By addressing limitations observed in prior studies and demonstrating practical applicability, this research contributes to advancing stock market prediction methodologies, offering valuable insights for investors and traders.